Penggunaan Metode Mind Mapping untuk Meningkatkan Kompetensi Menulis Karangan Siswa Kelas XII SMK Negeri 2 Garut - Empong Saodah (EduInovasi: Journal of Basic Educational Studies, 2022)
Researchers tried to use the mind mapping method to overcome some of the problems that occurred. The researcher tried this method because the researcher had attended training and read a book on Quantum Teaching and Learning by Bobbry D'botter at a private high school in Cibinong, Bogor Regency. In the training and the book, the material for the mind mapping method was very interesting. The research method used is quantitative and qualitative methods. Quantitative methods are used to determine how much student learning outcomes or achievement after using this mind mapping method. And qualitative methods are used to find out how the results of students' interest tests in Indonesian subjects through filling out questionnaires, before and after the implementation of the mind mapping method in this class. There are students who like the mind mapping method, some are just ordinary. Most students said it was easier to write an essay by making a mind map first. No one said it was getting dizzy anymore. What's interesting about mind mapping is the image, color and manufacture. Group study is preferred. With more intensive monitoring, all students are willing to work. The mind mapping method is very necessary in learning Indonesian, especially in the competence of writing essays. By making an outline in the form of a mind map that can be drawn and colored at will, it can motivate students to express their ideas through various images and colors. Mind mapping can also generate ideas, making it easier for students to write essays. Keywords: Mind Mapping, Competence, Writing Essay, Students